1997
DOI: 10.1139/z97-068
|View full text |Cite
|
Sign up to set email alerts
|

Trophic relationships of albatrosses associated with squid and large-mesh drift-net fisheries in the North Pacific Ocean

Abstract: The diets of Laysan (Diomedea immutabilis) and black-footed albatrosses (D. nigripes) killed in squid and large-mesh drift nets in the transitional zone of the North Pacific Ocean were investigated by examining the contents of the digestive tracts and determining δ13C and δ15N values in breast-muscle tissue. The results show that (i) the combined prey of the two species of albatross consists of over 46 species of marine organisms including coelenterates, arthropods, mollusks, fish, and marine mammals; (ii) bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 21 publications
3
47
0
Order By: Relevance
“…The isotope values we recorded from the liver of shearwaters and their prey in this study are comparable to those found in the pectoralis muscle tissues of short-tailed shearwaters incidentally captured in the large-mesh driftnet (Gould et al 2000) and gillnet (Minami et al 1995) (Cherel et al 2005b). These contrasts could be related to and originate from different isotopic values in the waters of the Antarctic ecosystem compared to that of the eastern Bering Sea, in the prey consumed, and/or differences in tissues sampled.…”
Section: T Inermissupporting
confidence: 80%
See 1 more Smart Citation
“…The isotope values we recorded from the liver of shearwaters and their prey in this study are comparable to those found in the pectoralis muscle tissues of short-tailed shearwaters incidentally captured in the large-mesh driftnet (Gould et al 2000) and gillnet (Minami et al 1995) (Cherel et al 2005b). These contrasts could be related to and originate from different isotopic values in the waters of the Antarctic ecosystem compared to that of the eastern Bering Sea, in the prey consumed, and/or differences in tissues sampled.…”
Section: T Inermissupporting
confidence: 80%
“…Based upon number, volume, and frequency of occurrence of prey items, the IRI was calculated for each study location within each season following Gould et al (2000) and Pinkas et al (1971):…”
Section: Methodsmentioning
confidence: 99%
“…In earlier publications this beak type was identified as from various species in the genus Gonatus (Table 3; see Clarke 1986, Fiscus et al 1989. In more recent publications, especially the reports on the stomach contents of albatrosses from the North Pacific (Gould et al 1997) and beaked whales from Japan (Walker et al 2002), similar beaks provisionally were assigned to the squid genus Galiteuthis, a member of the family Cranchiidae. Because both genus and species identifications remain in question we have chosen to enclose the name in quotation marks.…”
Section: Gonatus Berryi Naef 1923mentioning
confidence: 99%
“…North Pacific albatrosses are opportunistic foragers and consume a wide variety of prey using flexible foraging tactics (Harrison et al, 1983;Gould et al, 1997;Tickell, 2000;Conners et al, 2015); therefore, collecting a library of all potential prey species for lipid analysis would be both impractical and quantitatively unfeasible given limitations of the QFASA model itself. However, since the fatty acid composition of an organism is influenced by its feeding ecology (Budge et al, 2006), collecting species from across the range of functional groups regularly consumed by a predator theoretically should represent the range of lipids consumed by the predator.…”
Section: Compiling a Lipid Library Of Potential Prey Itemsmentioning
confidence: 99%
“…To effectively use QFASA to discriminate fisheries-associated diet from non-anthropogenic diet, lipids that compose fisheriesassociated resources must be biochemically distinct from the diet component unrelated to fisheries. North Pacific albatross are predominately surface scavengers and not known to hunt large, strong, and agile epipelagic fish species that are associated with fisheries activities, such as swordfish, tuna, and mackerel (Gould et al, 1997;Walker and Fitzgerald, 2012;. Thus, we approached this study feeling confident that for this particular predator-prey system, the resources we classified as fisheries-associated would be biochemically distinct from the natural diet component.…”
Section: Introductionmentioning
confidence: 99%